The Influence of Lesson Study Strategy on Teachers’s Pedagogical Quality in All State Madrasah Aliyah of Medan - Indra Prasetia; Akrim Akrim; Sulhati Sulhati; Burhanuddin Burhanuddin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study were : (1) to learn pedagogical strategies teachers who follow the guidance of teacher with lesson study and coaching strategies with MGMP convensional teacher,  (2) to determine the interaction between teacher coaching strategies with lesson study and strategies with teacher guidance MGMP conventional and subjects the teachers’ pedagogic competence, (3) to find pedagogical english teacher who followed a strategy with teacher guidance conventional MGMP, (4) to learn pedagogical math teacher who followed a strategy of coaching teachers with pedagogical lesson study and mathematics teachers who follow the strategy with teacher guidance conventional MGMP. This study is quasi-experimental research. The number of samples were 60 teachers. The tecnique of determining the sample is done by random sampling. Research hypptheses were tested using Anova 2 ways used before Anova first tested the data analysis requirements of the test for normality of data using Lillieofors test, and homogeneity of variance using the test Bartlet.